Mediterranean diet and other dietary patterns in association with biological aging in the Moli-sani Study cohort. Issue 5 (May 2022) - Esposito, Simona; Gialluisi, Alessandro; Costanzo, Simona; Di Castelnuovo, Augusto; Ruggiero, Emilia; De Curtis, Amalia; Persichillo, Mariarosaria; Cerletti, Chiara; Donati, Maria Benedetta; de Gaetano, Giovanni; Iacoviello, Licia; Bonaccio, Marialaura; et al.
Summary: Background & aims: Biological age (BA) is the hypothetical underlying age of an organism and has been proposed as a more powerful predictor of health than chronological age (CA). The difference between BA and CA (Δage) reflects the rate of biological aging, with lower values indicating slowed-down aging. We sought to compare the relationship of four a priori–defined dietary patterns, including a traditional Mediterranean diet (MD) and three non-Mediterranean diets, with biological aging (Δage) among Italian adults. We also examined distinctive nutritional traits of these diets as potential mediators of such associations. Methods: Cross-sectional analysis on a sub-cohort of 4510 subjects (aged ≥35 y; 52.0% women) from the Moli-sani Study (enrolment, 2005–2010). Food intake was recorded by a 188-item semi-quantitative food-frequency questionnaire. A Mediterranean diet score (MDS) was used as exposure and compared with non-Mediterranean dietary patterns, i.e. DASH (Dietary Approaches to Stop Hypertension), Palaeolithic and the Nordic diets. A Deep Neural Network based on 36 blood biomarkers was used to compute BA and the resulting Δage (BA-CA), which was tested as outcome in multivariable linear regressions adjusted for clinical factors, lifestyles and sociodemographic factors. Results: In a multivariable-adjusted model, 1 standard deviation increase in the MDS was inversely associated with Δage (β = −0.23; 95%CI -0.40, −0.07), and similar findings were observed with the DASH diet (β = −0.17; 95%CI -0.33, −0.01). High dietary polyphenol content explained 29.8% (p = 0.04) and 65.8% (p = 0.02) of these associations, respectively, while other nutritional factors analysed (e.g. dietary fibre) were unlikely to be on the pathway. No significant associations were found with either the Palaeolithic or the Nordic diets. Conclusions: Increasing adherence to either the traditional MD or the DASH diet was associated with delayed biological aging, possibly through their high polyphenol content.